SARS-CoV-2 infection risk among 77, 587 healthcare workers: a national observational longitudinal cohort study in Wales, United Kingdom, April to November 2020. (December 2022) - Hollinghurst, Joe; North, Laura; Szakmany, Tamas; Pugh, Richard; Davies, Gwyneth A; Sivakumaran, Shanya; Jarvis, Rebecca; Rolles, Martin; Pickrell, W Owen; Akbari, Ashley; Davies, Gareth; Griffiths, Rowena; et al.
Objectives: To better understand the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among healthcare workers, leading to recommendations for the prioritisation of personal protective equipment, testing, training and vaccination. Design: Observational, longitudinal, national cohort study. Setting: Our cohort were secondary care (hospital-based) healthcare workers employed by NHS Wales (United Kingdom) organisations from 1 April 2020 to 30 November 2020. Participants: We included 577, 756 monthly observations among 77, 587 healthcare workers. Using linked anonymised datasets, participants were grouped into 20 staff roles. Additionally, each role was deemed either patient-facing, non-patient-facing or undetermined. This was linked to individual demographic details and dates of positive SARS-CoV-2 PCR tests. Main outcome measures: We used univariable and multivariable logistic regression models to determine odds ratios (ORs) for the risk of a positive SARS-CoV-2 PCR test. Results: Patient-facing healthcare workers were at the highest risk of SARS-CoV-2 infection with an adjusted OR (95% confidence interval [CI]) of 2.28 (95% CI 2.10–2.47). We found that after adjustment, foundation year doctors (OR 1.83 [95% CI 1.47–2.27]), healthcare support workers [OR 1.36 [95% CI 1.20–1.54]) and hospital nurses (OR 1.27 [95% CI 1.12–1.44]) were at the highest risk of infection among all staff groups. Younger healthcare workers and those living in more deprived areas were at a higher risk of infection. We also observed that infection rates varied over time and by organisation. Conclusions: These findings have important policy implications for the prioritisation of vaccination, testing, training and personal protective equipment provision for patient-facing roles and the higher risk staff groups.